2007
DOI: 10.1097/01.prs.0000264396.03452.62
|View full text |Cite
|
Sign up to set email alerts
|

Management of Benign Tumors of the Adolescent Breast

Abstract: Although 99 percent of breast lesions in female adolescents are benign tumors, surgical intervention is commonly required. This article reviews the differential diagnosis, evaluation, and management of these benign tumors. A modified surgical technique for resection of large fibroadenomas and reconstruction of the remaining breast is described. The authors review the approach to five specific breast lesions: fibroadenomas, phyllodes tumors, juvenile hypertrophy, inflammatory processes, and premature breast dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
1
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 19 publications
0
74
1
17
Order By: Relevance
“…6 El rápido crecimiento podría provocar la compresión del tejido circundante, el deterioro de la estructura de la mama, la retracción del pezón y la expansión de las venas superficiales.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…6 El rápido crecimiento podría provocar la compresión del tejido circundante, el deterioro de la estructura de la mama, la retracción del pezón y la expansión de las venas superficiales.…”
Section: Discussionunclassified
“…Raramente son tumores malignos y la opción quirúrgica debe ser la excisión con conservación de la mama. 1,6,7 Asimismo, en el diagnóstico diferencial deben tenerse en cuenta los tumores filoides, la hipertrofia mamaria juvenil, el lipoma gigante, el hamartoma de la mama, los procesos inflamatorios, los quistes gigantes y el adenocarcinoma. 3,6,7,9,10 Los fibroadenomas gigantes pueden clasificarse como juveniles y adultos en cuanto a la edad de aparición, y como simples y complejos según el aspecto histológico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Accurate diagnosis is necessary before surgery; mammography is needed to exclude any underlying tumour. However, some authors require surgery be carried when the breasts have fully developed since this may result in avoidance of multiple operations [13,14]. Studies by Agbenorku et al from Komfo Anokye Teaching Hospital (KATH) revealed an increase in the number of patients presenting with symptomatic macromastia in the Plastic Surgery Unit of KATH [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Complete local excision with sparing of breast tissue, as done in our case is often the treatment modality of choice. To excise it, numerous surgical techniques, such as conventional local excision, reduction mammoplasty, or inframammary excision, round-block technique have been reported, 28,29 The biological behavior of the giant fibroadenoma is usually benign. It may recur after complete excision however, the chances of recurrence become less after third decade of life.…”
mentioning
confidence: 99%